Diffusion-controlled growth of aggregates in layer-by-layer films of poly(o-methoxyaniline) - De Souza, N. C.; Silva, JR; Rodrigues, C. A.; Hernandes, A. C.; Costa, L. D.; Giacometti, J. A.; Oliveira, O. N. (Elsevier B.V., 2003)
The adsorption process in layer-by-layer (LBL) films of poly(o-methoxyaniline) alternated with poly(vinyl sulfonic acid) is explained using the Avrami equation. This equation was used due to its mathematical simplicity and adequate description of experimental data in real polymer systems. The Avrami parameters are a convenient means to represent empirical data of crystallization, and if microscopic knowledge is available these parameters can also be associated with adsorption mechanisms. The growth of spherulites in the LBL films was studied as a function of time using atomic force microscopy and the data were used to estimate the number and radii of aggregates, from which the Avrami parameters were determined. We find that the adsorption mechanism may correspond to a tri dimensional, diffusion-controlled growth, with increasing nucleation rate, consistent with results from kinetics of adsorption.
Keywords: polyaniline and derivatives; atomic force microscopy